LAND GRABBING AS UNLAWFUL ACT - Catherine Susantio; Velliana Tanaya; Cassey Regina Salamintargo (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2022)
Land cases in Indonesia are one of the most common types of cases in Indonesia. The forms of land cases that often arise are related to land grabbing, namely illegal taking of land belonging to other party. An example of a land grabbing case can be seen in the Supreme Court Decision Number 1071 K/PDT/2020 where the Plaintiff is the rightful owner of a piece of land with property rights in Tanjung Jabung Barat Regency, Jambi Province as proven by the Certificate of Ownership, but then Defendant I came to take the land belonging to the Plaintiff by constructing a building on the land without a permit and refusing to move even though it has been given a warning, so that the Plaintiff feels aggrieved. Therefore, the author intends to find out how an act can be classified as against the law and what kind of compensation arrangements are in accordance with applicable regulations. The research method used is normative legal research method and the approach used is law approach and case approach. The results showed that land grabbing done by Defendant I could be classified as an act against the law because all the elements had been fulfilled; while related to losses due to unlawful acts in the form of land grabbing, the most appropriate compensation is the return of the Plaintiff’s condition to its original state.